The Impact of Social Media on Changes in Behavior and Morality of Adolescents from the Perspective of Islamic Education - Syahria Wahda; Febby Meilia Br. S. Meliala; Melinda Isa Bella Tarigan; Nazwa Desilhan Maha; Hapni Laila Siregar (Generasi Sains Indonesia, 2026)
This study aims to examine the impact of social media usage on students’ behavioral changes and moral orientation within the framework of Islamic education. A quantitative descriptive approach was employed using a structured questionnaire distributed to 50 university students. The data were analyzed using descriptive statistical techniques to identify patterns of social media use, behavioral effects, and moral tendencies. The findings reveal that social media plays a dual role. On the one hand, it supports learning, information access, and personal development. On the other hand, it contributes to reduced study time, increased consumptive behavior, and changes in communication patterns. Despite these challenges, students demonstrate strong moral awareness, particularly in maintaining ethical communication and avoiding misinformation. Islamic education emerges as a moderating framework that guides students’ digital behavior and reinforces moral responsibility. The novelty of this study lies in its integration of behavioral analysis with an Islamic educational perspective, positioning religious values as a moderating factor in digital ethics. The study implies the importance of combining digital literacy with value-based education to promote responsible social media use among students.